(untitled) (Tribhuvan University Journal of Food Science and Technology, 2022)
This study was aimed to evaluate the effect of EDTA blanching, NaCl blanching, and barley sprouts addition on the reduction of oxalates in starfruits juice. The effect of EDTA (0-0.6%), NaCl (0-10%), and sprouts (0-3%) treatments was evaluated by response surface methodology. EDTA, NaCl, and sprouts treatments had significant effects (p<0.05) on oxalate reduction. EDTA and NaCl treatments during blanching had a quadratic effect on the reduction of oxalate content of starfruit juice, while the addition of sprouts had a linear effect. Juice treated with all three factors had the maximum reduction, which was significantly higher (p<0.05) than individual treatments. The oxalates content was reduced to 6 mg/100 ml which is comparable to carrot and grapes juices and is considered as a normal oxalates level. Amongst the two factors treatment, the combination of EDTA and NaCl treatment had a significantly high reduction (p<0.05) as compared to other combinations. No significant difference (p>0.05) was obtained between the samples treated with EDTA (0.495%) or NaCl (10%) treatment in combination with sprouts addition. The regression expression for the oxalates reduction in response to these treatments was derived and validated.